2011
DOI: 10.1017/s0007114511004636
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary patterns in pregnancy and fetal growth in Japan: the Osaka Maternal and Child Health Study

Abstract: Maternal nutritional status during pregnancy is an important determinant of fetal growth. Although the effects of several nutrients and foods have been well examined, little is known about the relationship of overall maternal diet in pregnancy to fetal growth, particularly in nonWestern populations. We prospectively examined the relationship of maternal dietary patterns in pregnancy to neonatal anthropometric measurements at birth and risk of small-for-gestational-age (SGA) birth among 803 Japanese women with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
133
4
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(151 citation statements)
references
References 40 publications
10
133
4
4
Order By: Relevance
“…In previous studies, a maternal Western diet (28) and wheat products diet (29) during pregnancy were shown to be associated with a lower birth weight, which in turn could alter later body composition (30,31). On the basis of the phenomenon of fetal programming, which emphasizes prenatal nutrition as a key determinant for the increased risk of diseases later in life (5), we hypothesized that maternal diet during pregnancy could have a substantial influence on a child's body composition.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, a maternal Western diet (28) and wheat products diet (29) during pregnancy were shown to be associated with a lower birth weight, which in turn could alter later body composition (30,31). On the basis of the phenomenon of fetal programming, which emphasizes prenatal nutrition as a key determinant for the increased risk of diseases later in life (5), we hypothesized that maternal diet during pregnancy could have a substantial influence on a child's body composition.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary patterns considering the overall combinations of food groups and nutrients [24] among pregnant women have been studied using factor analysis or principal component analysis [25,26,27,28], reduced rank regression [29,30,31], cluster analysis [32,33], index analysis [7,8,9,34,35,36], or latent class analysis [37,38] in relation to small-for-gestational-age infants or pre-term births. To the best of our knowledge, there has been no research investigating the overall inflammatory potential of diet during pregnancy in relation to pre-pregnancy BMI.…”
Section: Introductionmentioning
confidence: 99%
“…As a modifiable factor, dietary patterns may be more applicable to clinical and pregnant health interventions (Xuyang et al, 2016). Being born with low birth weight (LBW) is generally recognized as a disadvantage for the infant, increasing the risk of early growth retardation, fast catch up growth, infectious disease, developmental delay, and death during infancy and childhood (Edmund and Bahl, 2006;Marte et al, 2014;Englund et al, 2014;Okubo et al, 2012;). Earlier publications have shown that dietary practices characterized with nutrient-rich foods were linked with bigger birth size outcomes (Englund et al, 2014;Wolff and Wolff, 1995).…”
Section: Introductionmentioning
confidence: 99%